Motivasi dan Pencapaian Belajar Grammar Bahasa Inggris Melalui Hipnolearning Bagi Mahasiswa Tahun Pertama Pada Jurusan Bahasa Inggris - Abd Halim; Muh. Tahir (Seminar Nasional LP2M UNM, 2019)
This research aims to explore the effectiveness of hypnolearning in learning English grammar and the students’ motivation during learning grammar. This study is an experimental research involving one class of Business English students by using dependent (paired) sample t-test.  The instrument used to collect data were tests of grammar and questionnaires for motivation data. Based on the research results, it was found that there was a significant differences between the mean of the students’ grammar knowledge before and after treatment that’s p-value 0,00 was smaller than significant level 0,05 (5%). This means that the hypnolearning was effective for the students for learning English grammar.  Besides, the students’ motivation in learning grammar during hypnolearning implementation was commonly strong. It may be caused by some factors namely lecturer’s personality, short story usage, visualization and refreshment.